Membagun Pendidikan 4.0: Peran Vital Teknologi dalam Meningkatkan Kualitas Pembelajaran - Nasution, Julia Ningsih; Putri, Anggi Emalia; Lubis, Yulianti; Siagian, Rezeky Tua; Umar, Andi Taufiq (LPPM Institut Pendidikan Nusantara Global, 2024)
The era of Industrial Revolution 4.0 brings new challenges and opportunities to education. To ensure appropriate learning with the progress of the Industrial Revolution 4.0 educators must design appropriate learning methods, models, and strategies. This study aims to examine the important role of learning in improving the quality of education and produce superior generations with Noble, creative, and innovative characters. Through the study of literature by collecting a variety of related literature, the results of this study show that technology in Education 4.0 not only increases efficiency and accessibility, but allows access to global educational resources in seconds, expanding the scope of learning and enabling greater personalization. In addition, a technology-driven learning approach allows for more active interaction between students, teachers, and learning content, promoting collaboration, discussion, and creativity. These changes also include the utilization of technology in testing and assessment, where digital tools provide the ability to evaluate students ' understanding more thoroughly and accurately.